Assessment of contamination of soil due to heavy metals around coal fired thermal power plants at Singrauli region of India - Agrawal P.; Mittal A.; Prakash R.; Kumar M.; Singh T.B.; Tripathi S.K. (My University, 2025)
In the present study, an attempt was made to measure contamination of soil around four large coal-based Thermal Power Plants. The concentration of Cadmium, Lead, Arsenic and Nickel was estimated in all four directions from Thermal Power Plants. The soil in the study area was found to be contaminated to varying degrees from coal combustion byproducts. The soil drawn from various selected sites in each direction was largely contaminated by metals, predominantly higher within 2-4 km distance from Thermal Power Plant. Within 2-4 km, the mean maximum concentration of Cadmium, Lead, Arsenic and Nickel was 0.69, 13.69, 17.76, and 3.51 mg/kg, respectively. It was also observed that concentration was maximum in the prevalent wind direction. The concentration of Cadmium, Lead, Arsenic and Nickel was highest 0.69, 13.23, 17.29 and 3.56 mg/kg, respectively in west direction where wind was prevalent. © 2010 Springer Science+Business Media, LLC.